Functional Characteristics of Lactobacillus and Yeast Single Starter Cultures in the Ripening Process of Dry Fermented Sausage - Liu, Yingli; Wan, Zhen; Yohannes, Kalekristos Woldemariam; Yu, Qinglin; Yang, Ziyan; Li, Hongyan; Liu, Jie; Wang, Jing (Frontiers in Microbiology, 2021)
Dry fermented sausage is popular among the world because of its rich nutrition and unique flavor. Starter cultures play an important role in the quality of dry fermented sausage. In this study, probiotics lactic acid bacteria Lactobacillus delbrueckii N102, Latilactobacillus sakei H1-5, Debaryomyces hansenii Y4-1, and Wickerhamomyces anomalus Y12-3 were isolated from food-borne materials. The physicochemical properties, microbial populations, TBARS, lipolysis, proteolysis, and volatile flavor compounds of dry fermented sausages with different starter cultures were evaluated comparatively during the ripening process. The results showed that both L. delbrueckii N102 and L. sakei H1-5 grow well and could rapidly reduce the pH value of the products. At the same time, they could significantly reduce the number of Enterobacter putrefaciens, so as to ensure the safety of the products. In addition, the strains N102 promoted the formation of flavor compounds 2,3-butanedione, 3-hydroxy-2-butanone, and carnosine, whereas taurine content of batch H1-5 was significantly increased, while yeast y4-1 and y12-3 could also grow faster in sausage and promoted the esters and alcohols formation such as ethyl acetate and linalool, with the formation of γ-aminobutyric acid by y4-1. Compared with lactic acid bacteria, yeasts showed to contribute more in flavor formation and effective inhibition of lipid oxidation. The starter cultures played different roles in flavor contribution and had obvious differentiation in the ripening process of dry fermented sausage.